THE ROLE OF THE MADRASAH PRINCIPAL IN LEARNING QUALITY MANAGEMENT THROUGH A TRANSFORMATIONAL LEADERSHIP PERSPECTIVE IN MADRASAH IBTIDAIYAH - Nurul Hidayah; Meisuri Meisuri (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the role of madrasah principals in the management of learning quality from the perspective of transformational leadership in Madrasah Ibtidaiyah. Methods: The method used is qualitative research with a case study approach. The research subjects were madrasah principals, vice principals in charge of curriculum, teachers, and madrasah committees at three State Madrasah Ibtidaiyah in Bandar Lampung City, selected purposively based on A accreditation criteria and academic achievement. Data collection techniques included in-depth interviews, participatory observation, and document analysis. Data analysis was conducted using the Miles, Huberman, and Saldaña model through the stages of data condensation, data presentation, and drawing conclusions. Data validity was ensured through source triangulation and methodological triangulation. Results: The research findings indicate that madrasah principals who consistently practice transformational leadership are able to improve the quality of learning through four main channels, namely (1) building a shared vision that inspires the entire madrasah community; (2) developing teachers’ professional capacity through needs-based coaching; (3) the creation of an innovative and collaborative learning culture; and (4) the strengthening of a learning evaluation system oriented toward continuous improvement.